2010
DOI: 10.1097/ta.0b013e3181c0b67a
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Alone Versus Computed Tomography and Magnetic Resonance Imaging in the Identification of Occult Injuries to the Cervical Spine: A Meta-Analysis

Abstract: Reliance on CT imaging alone to "clear the cervical spine" after blunt trauma can lead to missed injuries. This study supports a role for the addition of MRI in evaluating patients who are obtunded, or unexaminable, despite a negative CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…3,4 There is published evidence available to support both contentions, although the level of quality in peer-reviewed studies is less than adequate. [1][2][3][4] While acknowledging that MRI can identify injuries missed by MDCT, many physicians argue that such findings are often clinically insignificant and unlikely to alter treatment plans.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…3,4 There is published evidence available to support both contentions, although the level of quality in peer-reviewed studies is less than adequate. [1][2][3][4] While acknowledging that MRI can identify injuries missed by MDCT, many physicians argue that such findings are often clinically insignificant and unlikely to alter treatment plans.…”
mentioning
confidence: 89%
“…Those who support the use of adjunct MRI counter that neither the status of the spinal cord nor the integrity of the spinal ligamentous structures can be comprehensively assessed without the use of magnetic resonance technology. 3,4 These physicians believe that the costs of treating a single case of iatrogenic spinal cord injury incurred because of a falsenormal computed tomography far outweigh charges related to the performance of adjunct MRI. The current literature fails to support the use of either imaging protocol as the conclusive diagnostic test for occult spinal trauma.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have addressed secondary MRI findings when the initial CT scan did not identify cervical instability [8][9][10]26]. A meta-analysis of Schoenfeld [27] including 1,550 patients found injuries in 6 % initially undetected on CT or radiography, but later detected by MRI altering treatment. Recent literature has suggested that MRI may be limited in detecting minor discoligamentous injuries: Brandenstein [28] found a false-negative rate of 0.2 % for unstable cervical spine injuries even though cervical spine clearance was performed by radiographs, CT scan and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] A meta-analysis including 11 studies with data from 1,550 patients showed that MRI results altered management in 6% of patients, of whom 5% continued collar immobilization and 1% (12 patients) required surgical intervention. 18 This meta-analysis has been contested, however, 19 because a nonobtunded cohort was included in the analysis. When restricting the findings to obtunded patients with normal neurologic examinations, only 2 of 1,085 patients (0.2%) required operative cervical spine intervention.…”
Section: Discussionmentioning
confidence: 99%